Protection against major catastrophes: An economic perspective - Lars Wenzel; André Wolf (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2013)
This paper intends to further understanding of catastrophic events by reviewing the economic literature on their effects as well as potential means of dealing with the corresponding risks and uncertainties. Since 2000, the world has seen a number of catastrophes including terrorist attacks in the United States and Europe, tsunamis in Southeast Asia and Japan as well as volcanic eruptions in Iceland. All of these have had significant impacts on human well-being and economic activity beyond the regional level. In an increasingly populous and globalized world, these types of events and their repercussions are likely to increase. Hence, it is important to ensure that government and private entities cooperate in an attempt to reduce risks of catastrophes.
Keywords: 330